Biosynthesis of polymalic acid in fermentation: advances and prospects for industrial application. (3rd April 2019) - Zou, Xiang; Cheng, Chi; Feng, Jun; Song, Xiaodan; Lin, Meng; Yang, Shang-Tian
Abstract: Some microorganisms naturally produce β-poly(l -malic acid) (PMA), which has excellent water solubility, biodegradability, and biocompatibility properties. PMA has broad prospective applications as novel biopolymeric materials and carriers in the drug, food, and biomedical fields. Malic acid, a four-carbon dicarboxylic acid, is widely used in foods and pharmaceuticals, as a platform chemical. Currently, malic acid produced through chemical synthesis and is available as a racemic mixture ofl - andd -forms. Thed -form malic acid exhibits safety concerns for human consumption. There is extensive interest to develop economical bioprocesses forl -malic acid and PMA production from renewable biomass feedstocks. In this review, we focus on PMA biosynthesis by Aureobasidium pullulans, a black yeast with a large genome containing genes encoding many hydrolases capable of degrading various plant materials. The metabolic and regulatory pathways for PMA biosynthesis, metabolic engineering strategies for strain development, process factors affecting fermentation kinetics and PMA production, and downstream processing for PMA recovery and purification are discussed. Prospects of microbial PMA and malic acid production are also considered.